"James Rorke Family Photo" - Rorke Family (1937)
James Rorke's family, outside having a cup of tea/coffee. From left: Yvonne (Rorke) Pratt, Kathleen (Forward) Rorke (mother), Patricia (Rorke) Yorke, James Ernest Rorke and James Rorke (father). James Rorke (1890-1947), son of James Addy Rorke and Mary (Wilcox) Rorke, was born 13 April 1890. He married Kathleen Forward (1894-1979), daughter of Ernest Edward Forward and Tryphena (Butt) Forward, on 23 May 1917, and had three children: Patricia (Rorke) Yorke (1918-), James Ernest Rorke (1919-2005) and Yvonne (Rorke) Pratt (1922-1998). Like his father, James Rorke worked with the family company, John Rorke and Sons, Limited. He died on 14 May 1947 in Carbonear, Newfoundland. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.